Molecular Characterization of Metanephric Adenoma, Epithelial Wilms Tumor, and Overlap Lesions: An Integrated Whole-exome and Transcriptome Sequencing Analysis. Issue 4 (6th April 2022) - Pan, Chin-Chen; Tseng, Chih-En; Kuroda, Naoto; Yano, Mitsutake; Yasuda, Masanori; Nagashima, Yoji; Yeh, Yi-Chen; Wang, Yu-Chao; Chang, Yen-Hwa; Epstein, Jonathan I.
Abstract : Metanephric adenoma (MA) and Wilms tumor (WT) represent 2 prototypes of primary renal neoplasms closely resembling embryonal renal tubules. Tumors with overlapping features may occur, requiring differential diagnoses between the 2. Evidence of divergent oncogenic pathways has been reported, suggesting that MA is driven by BRAF mutation while most WT is of the BRAF wild-type. We collected 4 MA cases, 3 cases of monophasic epithelial WT, and 1 overlap metanephric tumor that contains both conventional MA and high-grade components similar to epithelial WT. Whole-exome sequencing and whole transcriptome sequencing were performed to discover mutations, somatic copy number variation, and differential expression. The findings were compared with those of WT of the TARGET database (WT-TARGET). BRAF V600E mutation was detected in all MAs as well as the overlap tumor but was undetectable in all epithelial WTs and WT-TARGET. The overlap tumor showed an additional pathogenic mutation of SETD2 . Three frequent gene mutations observed in WT-TARGET were not common in epithelial WT, in which the mutations appeared sporadic. The profiles of recurrent copy number variations were all different among MA, epithelial WT, and WT-TARGET. Differential expression and unsupervised hierarchical cluster analyses revealed distinct clusters of the 3 categories. Remarkably, the overlap tumor coclustered with MA, separated from epithelial WT and WT-TARGET. The distinctiveness of MA and WT were demonstrated corresponding to BRAF -mutated and non– BRAF -mutated pathways from the molecular perspective. BRAF assay has diagnostic implication for overlap tumors.